The Quality of New Modes of Urban Production - Amouri, Radja; Dechaicha, Assoule; Alkama, Djamel (Indonesian Journal of Social Science Research, 2024)
The trend of housing quality has become more intricate and has expanded to encompass all aspects of habitat. There are several significant challenges related to improving housing, both socially and in terms of economic and environmental considerations. Discussing the quality of new production methods requires an analysis based on various traditional criteria, using convenient indicators such as cleanliness, stability, safety, comfort, durability, flexibility, and aesthetic appeal. The principal aim of this study is to provide an objective assessment of the quality of Participative Subsidized Housing (LPA) in the municipality of EL-Khroube in Algeria. The methodology employed integrates a field survey and a resident questionnaire to appraise the comfort level offered by this housing type as well as the level of resident satisfaction. The results of the on-site observation indicated that the living environment does not offer an adequate level of comfort. This finding was corroborated by the questionnaire results, which revealed a prevailing sentiment of dissatisfaction among residents. This dissatisfaction can be attributed to issues pertaining to interior comfort and a dearth of local infrastructure and facilities. The results of this study will assist housing stakeholders in enhancing this mode of production through a collaborative and participatory approach.